حقوق السجناء بمدينة أربيل - إقليم كوردستان العراق : دراسة فقهية تحليلية - سورجي، فرست محمد ملا
Imprisonment is considered the severest punishment after execution in Iraq, and it was revenge against criminals, then the idea is changed to reform and rehabilitation. The transformation of imprisonment from the end to the means. it is taken as a means to reform and rehabilitation. Institutions worked in this field, so they set the means, methods and tools of actors in the process of Reform and rehabilitation. Human soul can be considered as the most valuable asset that it possesses, and their freedom should be protected. That is why God Almighty has prescribed penalties as a deterrent to the criminal and the perpetrator as well as bids those who want to encroach on the property of others. Many economic and military crises in the Kurdistan Region - Iraq have been affected by the inability and ability to provide the rights of inmates and detainees. Subsequently, this research came to find out the origin of the problems facing prison departments, and how to deal with them and make solutions to them. The researcher chose Women and Children Reform Department in the city of Erbil as a topic for his research, following the inductive approach by collecting scientific materials on the issue of the rights of prisoners or inmates in The light of ancient and modern sources, especially the books written in the doctrine of Imam al-Shafi’I (may God have mercy on him). As it is the dominant doctrine in the Kurdistan Region of Iraq, then the curriculum Analytical study to study the opinions of jurists and analyze the basics which they have put in the issue of prisoners' rights, and the researcher has interviewed specialists such as judges, rulers, lawyers, and researchers in the public, social research in reform departments, using field study in courts, reform departments and the Bar Association, in the city of Erbil. The most deserving of the rights that should be provided is the establishment of an appropriate atmosphere for the process of reform and rehabilitation of inmates. The appropriate atmosphere under which all the rights mentioned in Iraqi legal system and Islamic jurisprudence are included. Thus, It is necessary to take care of these juveniles more than other inmates .